1995
DOI: 10.1128/aem.61.7.2540-2547.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and partial characterization of regulated promoters from Lactococcus lactis Tn917-lacZ integrants with the new promoter probe vector, pAK80

Abstract: Transposon Tn917-LTV1 was used to produce a collection of Lactococcus lactis strains with fusion of a promoterless lacZ gene to chromosomal loci. Screening 2,500 Tn917-LTV1 integrants revealed 222 that express ␤-galactosidase on plates at 30؇C. Pulsed-field gel electrophoresis revealed Tn917-LTV1 insertions in at least 13 loci in 15 strains analyzed. Integrants in which ␤-galactosidase expression was regulated by temperature or pH and/or arginine concentration were isolated. In most cases, the regulation obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(68 citation statements)
references
References 39 publications
0
68
0
Order By: Relevance
“…The pH-and growth phase-regulated promoter P170 from L. lactis MG1363 was originally isolated on a 9.7 kb DNA fragment (Israelsen et al, 1995). This former study also showed that low pH and stationary phase co-dependency were required for high promoter activity.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The pH-and growth phase-regulated promoter P170 from L. lactis MG1363 was originally isolated on a 9.7 kb DNA fragment (Israelsen et al, 1995). This former study also showed that low pH and stationary phase co-dependency were required for high promoter activity.…”
Section: Resultsmentioning
confidence: 88%
“…To investigate whether a gene was transcribed from the P170 promoter, inverse PCR was used to amplify the DNA region located downstream of the Tn917 insertion point of integrant PA170 (Israelsen et al, 1995) Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The 358-bp PCR fragment corresponding to 257 bp upstream and 98 bp downstream the ATG codon of ytgB, which is the ¢rst gene of the operon containing ytgH was cloned into the SmaI site of the pAK80 plasmid [6]. This transcriptional fusion was transformed in L. lactis IL1403 resulting in strain NVlac.…”
Section: Construction Of the Transcriptional Fusionmentioning
confidence: 99%
“…No obvious 335 box was present in this promoter region. A 358-bp fragment including this promoter was cloned in front of the reporter genes lacL^lacM (encoding the L-galactosidase of Leuconostoc mesenteroides) in the low copy number plasmid pAK80 [6]. Fig.…”
Section: Mapping the Transcriptional Start Sites Of Ytgh Operonmentioning
confidence: 99%
“…After electroporation into L. lactis MG1363, growth of transformants was accompanied in both cases by the development of a deep blue colour on GM17 plates containing Xgal, indicating b-gal activity and, therefore, the presence of active promoters. To quantify the levels of b-gal activity, Miller assays were performed on liquid cultures of both strains according to the method of Israelsen et al (1995). The levels of b-gal were in the same range for both cultures, with high levels of expression from both promoters ( Fig.…”
Section: Overexpression Of Ltnr Results In An Increase In Sensitivitymentioning
confidence: 99%